1992
DOI: 10.1016/0042-6822(92)90041-m
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of the spike protein gene of murine coronavirus variants: Study of genetic sites affecting neuropathogenicity

Abstract: Mouse hepatitis virus (MHV), a coronavirus, causes encephalitis and demyelination in susceptible rodents. Previous investigations have shown that the MHV spike (S) protein is a critical determinant of viral tropism and pathogenicity in mice and rats. To understand the molecular basis of MHV neuropathogenesis, we studied the spike protein gene sequences of several neutralization-resistant variants of the JHM strain of MHV, which were selected with monoclonal antibodies (MAbs) specific for the S protein. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 38 publications
5
69
0
Order By: Relevance
“…infections (34). Age-matched (5-7 wk old) C57BL/6 mice (H-2 b background) were used for all experiments (National Cancer Institute, Bethesda, MD).…”
Section: Virus and Micementioning
confidence: 99%
“…infections (34). Age-matched (5-7 wk old) C57BL/6 mice (H-2 b background) were used for all experiments (National Cancer Institute, Bethesda, MD).…”
Section: Virus and Micementioning
confidence: 99%
“…Each virus was purified by 3 rounds of limited dilution, expanded, and cleared by centrifugation at 2,000 ϫ g for 25 min at 4 C. The supernatant containing viral particles was used for RNA extraction by mixing 0.25 ml of virus suspension with 0.75 ml of Trizol . b Half of the pelleted RNA was used for one reverse transcription reaction, 26 23 where GF1 were 5Ј-ATGTTCA-AGGTCCTCATAATTACC-3Ј (1-24) and GR1 were 5Ј-TAATGATCAAAGAACCTATCATCAC-3Ј (1,847-1,871). The reaction mixture was denatured at 94 C for 4 minutes, followed by 30 cycles of amplification at 94 C for 45 seconds, 52 C for 60 seconds, and 72 C for 90 seconds, with a final extension at 72 C for 10 minutes.…”
Section: Sera Sampling (mentioning
confidence: 99%
“…Results from previous studies have indicated that the S gene of coronaviruses plays an important role in virulence and pathogenicity (Taguchi et al, 1985 ;Dalziel et al, 1986 ;Fleming et al, 1986 ;Wege et al, 1988 ;Morris et al, 1989 ;Parker et al, 1989 ;LaMonica et al, 1991 ;Wang et al, 1992). Therefore, we investigated whether coronavirus replication in brain tissue of persistently infected Lewis rats results in an accumulation or selection of S gene variants.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that the S and HE proteins are important determinants for the neuropathogenicity of the virus and for its ability to infect a variety of cell types (Taguchi et al, 1985 ;Morris et al, 1989 ;Parker et al, 1989 ;Wang et al, 1992 ;LaMonica et al, 1991 ;Fazakerley et al, 1992 ;Yokomori et al, 1993). The S protein in particular elicits neutralizing antibodies, binds to cell receptors and causes cell fusion.…”
Section: Jhm-pi Using Rt-pcr Amplification Methods the S Gene Sequenmentioning
confidence: 99%